Adapting to Climate Change: Long-Term Effects of Drought on Local Labor Markets - Paulo Bastos; Matias Busso; Sebastian Miller (Inter-American Development Bank (IDB), 2013)
We examine the long-term impacts of drought on local labor markets in Brazil. Us- ing rainfall data going back over a century, we build contemporaneous and historical drought indices for more than 3,000 local areas, and examine them in conjunction with five waves of population census data spanning 1970-2010. Results from a difference- in-differences design reveal that increased drought frequency in the previous decade reduces local value added, employment and wages in the agricultural sector; leads to job losses and pay cuts in the local manufacturing and services sectors; and induces out-migration, especially among younger cohorts, leading to relative population de- cline. These findings are in line with standard general-equilibrium theory featuring imperfect labor mobility across space.
Keywords: J61; N96; O15; Q54; R11; R23; 330